BANDUNG CONCERT HALL - Pandapotan Robertino, Daniel
In Bandung, there is no place that can appropriately accommodate music concert. This concert hall project is located in a 16,000 sqm land on the east area of Bandung that is currently under development. The designed building has to become the representation of the area and stimulate the growth of building development in east Bandung. The designed building is a concert hall which can accommodate pop, rock, jazz, and classical music performance and has 2 auditoriums that can accommodate up to 1,300 people. The issues picked in this project are acoustic, circulation, and sound insulation. In addition to performance function, this building also has some support functions such as music course, rental studio, restaurant, café, retail, and management office. The building also has an amphitheater to accommodate informal outdoor performances. To solve the problems that are present, the comcept of harmony in simplicity is being used. This concept is applied to the design by creating a building whose elements are arranged in harmony so that it becomes a unique building. The building mass consists of 2 elips placed well-?balanced to make the building more emphasized than its sorroundings. The building façade is designed by combining static and dynamic shapes arranged harmoniously. The acoustic of the concert spaces are designed by adjusting the shape of the auditoriums and placing the acoustic panels. The auditorium for classical music is separated to the auditorium for pop, rock, and jazz concert which is designed to be more flexible and has different requirements.